Wybór prawa dla umowy o pracę: Glosa do wyroku Trybunału Sprawiedliwości Unii Europejskiej z dnia 15 lipca 2021 r. w sprawach połączonych DG, EH c/a SC Gruber Logistics SRL (C-152/20) oraz Sindicatul Lucrătorilor din Transporturi, TD c/a SC Samidani Trans SRL (C-218/20) - Kurowski, Witold (Problemy Prawa Prywatnego Międzynarodowego, 2021)
This paper comments on a recent ruling concerning the choice of law to the individual employment contract according to the Rome I Regulation. In the judgement in the joined cases C–152/20 and C–218/20 (DG, EH v. SC Gruber Logistics SRL and Sindicatul Lucrătorilor din Transporturi, TD v. SC Samidani Trans SRL), the Court of Justice of the European Union (CJEU) provided the interpretation of Article 8 of the Rome I Regulation on two issues. At first, the EU Court was asked about the freedom of choice of law applicable to the individual employment contract if (a) national law required the inclusion of a clause into that contract under which the contractual provisions are supplemented by national law and (b) the contractual clause concerning that choice was drafted by the employer. The second issue was connected with the concept of the employee’s protection, under which the choice of law may not have the result of depriving the employee of the protection afforded to him (her) by provisions that cannot be derogated from by agreement, under the law that would have been applicable to the contract in the absence of choice. Regarding the first question, the CJEU admitted that the parties to an individual employment contract dispose of freedom to choose the law applicable to that contract, even if the contractual provisions are supplemented by national labour law under a (relevant) national provision, if “the national provision in question does not require the parties to choose national law as the law applicable to that contract”. Secondly, the Court found that the parties to an individual employment contract were “to be regarded as being, in principle, free to choose the law applicable to that contract, even if the contractual clause concerning that choice is drafted by the employer”. Therefore, the CJEU confirmed the application of the rules concerning the choice of law resulting from Article 3 of the Rome I Regulation to the individual employment contracts. Referring to the second issue of the commented ruling, the CJEU confirmed that Article 8 (1) of the Rome I Regulation must be interpreted as meaning that, where the parties have chosen the law governing the individual employment contract, the application of the law that would apply to the contract in the absence of choice must be excluded, with the exception of “provisions that cannot be derogated from by agreement”, if those provisions offer the employee concerned greater protection than those of the law chosen by the parties. The EU Court underlined that rules on the minimum wage could be treated as “provisions that cannot be derogated from by agreement” and the law that, in the absence of choice, would be applicable should decide about it. Unfortunately, it is necessary to follow the commented judgment’s justification to correctly understand the concept of an employee’s protection applied in Article 8 (1) of the Rome I Regulation. The thesis of the ruling in this regard seems to be too laconic, and it can be misinterpreted.